Relationship Between Knowledge of the Role of Motivation and Work Period of Posyandu Cadres Towards the Use of Anthropometric Devices at UPTD Puskesmas Topo - Dini Anggraeny; Nur Susan Iriyanti Ibrahim; Bau Kanang (Lembaga Pengembangan Kinerja Dosen, 2025)
Anthropometry is a direct technique for evaluatingnutritional status, especially protein and energy levels of the body. One of the efforts to develop competent and skilled cadres in anthropometric measurements is through training techniques. To determine the relationship between knowledge, role, motivation and length of service of Posyandu cadres towards the use of anthropometric tools at the Topo Health Center UPTD.Method:This type of research is observational analytic using Cross Sectional Study. The research sample amounted to 30 cadres from 3 active posyandu. Data analysis used the Statistical Program For Social Science (SPSS) version 16.0.Results:Chi Square Testshows that there is no relationship between cadre knowledge and the use of anthropometric tools based on the measurement of the foot scale and stadiometer (p-value> 0.05). There is a relationship between cadre knowledge and the use of anthropometric tools based on the measurement ofLiLa, infantometer, and head circumference (p-value <0.05). While the relationship between work period and the use of anthropometric tools and the relationship between motivation and the use of anthropometric tools is not related (p-value> 0.05). Conclusion: There is a significant relationship between cadre knowledge and the use of anthropometric tools (measurement ofLiLa, infantometer, and head circumference). There is no significant relationship between work period and the use of anthropometric tools, as well as motivation and the use of anthropometric tools. Suggestion: it is hoped that cadre training will be held frequently and will be improved and more active in using anthropometric tools.